Enlightenment and ontology. Russian Preclassic Enlightenment: Kireyevsky - Kuznetsov, Vsevolod (Sententiae, 2017)
This work continues a series of articles The Enlightenment and ontology. It investigates the ontological component of the Russian Preclassic Enlightenment. The author claims that the Russian Enlightenment arises in the 30s-40s of XIX century. As the founders of the Russian Preclassic Enlightenment he considers Kireyevsky, Chaadayev and Herzen. This article considers the philosophy of Kireyevsky. Based on the concept of the nature and features of the Enlightenment, developed in the preceding articles, the author argues that Kireyevsky is a figure of the Enlightenment. The basic concept in the philosophy of Kireyevsky is the concept of education. It is a process of transformation of reality under the influence of education and the result of this process – a certain state of spirituality. The Russian Orthodox education formed the basis of Russian civilization and the very nature of the Russian people. The influence of Western education damaged the foundations of civilization and the nature of the people. To correct damage is possible by means of a new philosophy which should be based on the synthesis of Christian Orthodox and Western education. The aim of this project is to implement the utopia of holistic man. Kireyevsky also emphasizes the inextricable and essential link between the Russian Education and literature. This allows to consider Kireyevsky as the representative of the Enlightenment. The author also shows that Kireyevsky constructs two ontological models. The first model could be called ethnic and civilizational. Civilization is a phenomenon, able to change its own ontological status. The second model can be called prophetic. As a carrier of the sacred word, a writer appears as a prophet and lawgiver. His work provides the highest ontological status for society. The first model is new. The second model descends from the previous stages of development of the Russian Enlightenment. At the same time Kireyevsky tries to overshadow the traditional ontological model where the main role is played by the sacred tsar, even though the traditional model was basic then in Russia.